Features of the Behavior of a Plane Axisymmetric Mag-netic Fluid Drop in a Nonmagnetic Solvent and a Uni-form Magnetic Field - V. G. Bashtovoi; A. G. Reks; A. A. Zahadskaya (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The work is devoted to an experimental study of the process of dissolution of a magnetic fluid in a nonmagnetic solvent under the action of a uniform magnetic field. It is experimentally established that in a volume of magnetic fluid surrounded by a miscible solvent fluid, under the action of a uniform magnetic field, a mechanical movement arises, triggering deformation of this volume. Initially, the axisymmetric volume of the fluid takes an ellipsoidal shape, lengthening along the magnetic field direction. The main reason for this movement is the pressure differences in the magnetic fluid, caused by jumps and nonuniformities of the magnetic field at the interface between magnetic and nonmagnetic media. Simultaneously with the mechanical motion, the diffusion dissolution of the magnetic fluid occurs, which is also accompanied by the motion of the diffusion front at the interface between the fluids. The concentration gradients of magnetic particles that arise in this case cause gradients of the magnetization of the fluid and, as a consequence, gradients of the magnetic field intensity. Together, this triggers the appearance of a bulk magnetic force in the magnetic fluid, and the pressure gradients associated with it. The main regularities of this process have been established, viz. the dependence of change of the geometric characteristics of the volume and its deformation rate on time. It is shown that at the initial stage of the process, the rates of mechanical movement of the boundaries of the magnetic fluid volume are much higher than the rates of movement of the diffusion front. Thus, the initial rate of mechanical elongation of the droplet under the experimental conditions is 0.25 mm/min, and the diffusion front rate is 0.08 mm/min. Over time, these processes slow down and stop when the volume of the magnetic fluid is completely dissolved. Herewith, the mechanical elongation of the drop is the first to stop and, in the case under consideration, takes about ten minutes.